Função endócrina do interferon-tau durante o reconhecimento materno da gestação em ovinos - Antoniazzi, Alfredo Quites (2010)
The objective of the present study is to evaluate interferon-tau (IFNT) endocrine action in extra uterine tissues. The first approach consists of collecting samples from ewes on days 12, 13, 14 and 15 of the estrous cycle or early pregnancy. The second, consists of installing osmotic pumps to deliver a continuous concentration of recombinant ovine (ro) IFNT into the uterine vein for 24 or 72 hours. Our hypothesis is that endocrine release of IFNT into the uterine vein occurs as early as Day 13 of pregnancy. Also, that 24 and 72 hours infusion of roIFNT induces ISGs in the CL, liver and endometrium and IFNT has endocrine action on the CL to modulate major genes involved in luteolysis. Endometrium, liver, corpus luteum, uterine vein, jugular and uterine vein blood were collected from cyclic (NP) and pregnant (P) ewes on Days 12, 13, 14 and 15. Instalation of 24 and 72 hour pumps was done on Day 10 of the estrous cycle. Half were infused with BSA and the other half with roIFNT. Only in the 24 hour infusion, half of each group was challanged with a PGF injection at 12 hours following pump installation. Concentrations of progesterone in serum were similar on Days 12 and 13 and then declined (P<0.05) to less than 1 ng/ml in NP ewes between Days 14 and 15. Endometrial ISG15 mRNA increased (P<0.05) in P versus NP ewes by Day 13 and remained greater through Day 15. Endometrial ESR1 and OXTR mRNAs were up-regulated (P<0.05) in NP compared to P ewes by Day 14, and remained up-regulated on Day 15. Uterine vein ISG15 mRNA was not affected by pregnancy status. IFNAR1 and IFNAR2 mRNA were present in the CL, but did not change due to pregnancy status. ISG15 mRNA in CL and liver increased (P<0.05) by Day 14 and remained up-regulated on Day 15 in P compared to NP ewes. The expression of ESR1, OXTR, PTGFR, PTGER2, PTGER3 and PTGER4 did not change in the corpus luteum during Days 12, 13, 14 and 15 related to pregnancy status. Following the 24 hour infusion, ESR1, OXTR, PTGER2 and PTGER3 mRNA were not affected, but SLCO2A1 mRNA decreased (P<0.001) in BSA+PGF, roIFNT and roIFNT+PGF compared to BSA-infused ewes. PTGFR mRNA was down regulated (P<0.001) in roIFNT and roIFNT+PGF compared to BSA and BSA+PGF-infused ewes. PTGER4 mRNA was greater (P<0.05) in roIFNT and roIFNT+PGF compared to BSA, but not compared to BSA+PGF-infused ewes. After 72 hours, concentrations of progesterone did not differ in roIFNT- compared to BSA-infused ewes. ISG15 mRNA was induced in the CL, liver and endometrium in roIFNT- compared with BSA-infused ewes. Endocrine action of IFNT occurred through up-regulation of ISG15 mRNA in CL and liver by Day 14 of pregnancy. It is concluded that IFNT has endocrine effects on the CL between Days 13 and 14 of pregnancy and may protect the CL through mechanisms that are complementary, yet independent to its paracrine effects on the OXTR endometrial pathway.